Case Report: Aperiodic Fluctuations of Neural Activity in the Ictal MEG of a Child With Drug-Resistant Fronto-Temporal Epilepsy - van Heumen, Saskia; Moreau, Jeremy T.; Simard-Tremblay, Elisabeth; Albrecht, Steffen; Dudley, Roy WR.; Baillet, Sylvain (Frontiers in Human Neuroscience, 2021)
Successful surgical treatment of patients with focal drug-resistant epilepsy remains challenging, especially in cases for which it is difficult to define the area of cortex from which seizures originate, the seizure onset zone (SOZ). Various diagnostic methods are needed to select surgical candidates and determine the extent of resection. Interictal magnetoencephalography (MEG) with source imaging has proven to be useful for presurgical evaluation, but the use of ictal MEG data remains limited. The purpose of the present study was to determine whether pre-ictal variations of spectral properties of neural activity from ictal MEG recordings are predictive of SOZ location. We performed a 4h overnight MEG recording in an 8-year-old child with drug-resistant focal epilepsy of suspected right fronto-temporal origin and captured one ~45-s seizure. The patient underwent a right temporal resection from the anterior temporal neocortex and amygdala to mid-posterior temporal neocortex, sparing the hippocampus proper. She remains seizure free 21 months postoperatively. Histopathological assessment confirmed frank focal cortical dysplasia (FCD) type IIa in the MEG-defined SOZ, which was based on source imaging of averaged ictal spikes at seizure onset. We investigated temporal changes (inter-ictal, pre-ictal, and ictal periods) together with spatial differences (SOZ versus control regions) in spectral parameters of background brain activity, namely the aperiodic broadband offset and slope and assessed how they confounded the interpretation of apparent variations of signal power in typical electrophysiological bands.